Characterization and Engineering of the Adenylation Domain of a NRPS-Like Protein: A Potential Biocatalyst for Aldehyde Generation - Wang, Meng (American Chemical Society, 2014)
[Image: see text] The adenylation (A) domain acts as the first “gate-keeper” to ensure the activation and thioesterification of the correct monomer to nonribosomal peptide synthetases (NRPSs). Our understanding of the specificity-conferring code and our ability to engineer A domains are critical for increasing the chemical diversity of nonribosomal peptides (NRPs). We recently discovered a novel NRPS-like protein (ATEG_03630) that can activate 5-methyl orsellinic acid (5-MOA) and reduce it to 2,4-dihydroxy-5,6-dimethyl benzaldehyde. A NRPS-like protein is much smaller than multidomain NRPSs, but it still represents the thioesterification half-reaction, which is otherwise missed from a stand-alone A domain. Therefore, a NRPS-like protein may serve as a better model system for A domain engineering. Here, we characterize the substrate specificity of ATEG_03630 and conclude that the hydrogen-bond donor at the 4-position is crucial for substrate recognition. Next, we show that the substrate specificity of ATEG_03630 can be engineered toward our target substrate anthranilate via bioinformatics analysis and mutagenesis. The resultant mutant H358A increased its activity toward anthranilate by 10.9-fold, which led to a 26-fold improvement in specificity. Finally, we demonstrate one-pot chemoenzymatic synthesis of 4-hydroxybenzaldoxime from 4-hydroxybenzoic acid with high yield.